IMPACT OF ORAL HYGIENE PRODUCTS ON THE ORAL MICROBIOME AND SUSCEPTIBILITY TO THRUSH: A NARRATIVE REVIEW (Journal of Medical & Health Sciences Review, 2025)
By managing periodontal disorders, avoiding tooth cavities, and reducing bacterial loads, oral hygiene products are essential for preserving oral health. But there are concerns about how they may affect the delicate balance of the oral microbiome, which is a complex ecology of bacteria, fungus, and other microorganisms. The oral microbiota is essential for preserving homeostasis, promoting healthy digestion, and averting infections. Opportunistic infections, especially Candida albicans, the main cause of oral thrush, can proliferate as a result of disruptions brought on by dietary changes, antibiotics, or oral hygiene products. White lesions, inflammation, and discomfort are the hallmarks of thrush, which is most prevalent in immunocompromised people, the elderly, and newborns.This narrative review examines the connection between microbiome dynamics and oral hygiene products, with a particular emphasis on how these factors affect thrush susceptibility. While alcohol, chlorhexidine, and triclosan are efficient against dangerous bacteria, they can also accidentally diminish microbial diversity, which can lead to an overgrowth of Candida. On the other hand, substitutes like xylitol, essential oils, probiotics, and prebiotics exhibit microbiome-friendly qualities, specifically focusing on pathogenic microorganisms while maintaining microbial stability. There is also discussion of disruption mechanisms such pH change, reduced bacterial competition, and enhanced fungal adhesion.The study highlights the need of balanced dental hygiene habits, especially for vulnerable groups, and promotes the use of products that support the microbiome and less disruptive agents. Thrush and other fungal infections can be prevented by using these tactics to support microbial balance. Subsequent investigations ought to concentrate on the enduring consequences of oral hygiene products and novel formulations that maintain microbiome diversity and oral health.